Distribution of three geomagnetic components over Mizuho Plateau, Antarctica - Aiichiro Yoshimura; Yoshiaki Abe; Renji Naruse (National Institute of Polar Research, 1977)
Distributional maps of declination, inclination and total force of geomagnetism reduced to the epoch of 1970.0 are presented on the basis of the data obtained by the oversnow traverses during the period from 1968 to 1974 over Mizuho Plateau, East Antarctica. One of the local magnetic anomalies appears in a region to the southwest of Sandercock Nunataks and another between Syowa Station and Mizuho Camp. They coincide well with the regions where the large gravity anomalies are given.